2017
DOI: 10.18203/2349-2902.isj20172777
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT scan in evaluation and management of intestinal obstruction

Abstract: Background: Intestinal obstruction is one of the most common diseases in abdominal surgery. It can slowly lead to changes in intestinal structure and function, and in extreme cases it can be life-threatening. CT allows imaging of the abdominal contents outside the lumen, because of this advantage, the nature and site of the obstruction, especially extraluminal or intramural process, can be established.Methods: Prospective Hospital Based study. From January 2016 to November 2016 (11 months). 50 Patients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been observed that the small bowel is more frequently involved, accounting for 60%-85% of cases of intestinal obstruction with a four to five times less common involvement of the large bowel [1][2]. It occurs either due to mechanical obstruction or functional abnormality that results in the interruption of the normal passage of intraluminal contents [3]. Various causes of bowel obstruction have been identified, which can be categorized as extrinsic, intrinsic, or intraluminal based on their location [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the small bowel is more frequently involved, accounting for 60%-85% of cases of intestinal obstruction with a four to five times less common involvement of the large bowel [1][2]. It occurs either due to mechanical obstruction or functional abnormality that results in the interruption of the normal passage of intraluminal contents [3]. Various causes of bowel obstruction have been identified, which can be categorized as extrinsic, intrinsic, or intraluminal based on their location [4].…”
Section: Introductionmentioning
confidence: 99%
“…But in the last two decades, this surgical adage has lost its significance, especially with the advent of CT. More and more patients are now treated conservatively than surgically thus leading to decreased morbidity associated with a surgical procedure. 5 It was in 1972, that first CT scan for commercial use was introduced by British engineer Godfrey Hounsfield of EMI laboratories along with physicist Dr. Allan Cormack. He co-invented the technology with physicist Dr. Allan Cormack.…”
Section: Introductionmentioning
confidence: 99%